2019
DOI: 10.1016/j.gie.2018.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic magnetic sphincter augmentation versus double-dose proton pump inhibitors for management of moderate-to-severe regurgitation in GERD: a randomized controlled trial

Abstract: Patients with GERD with moderate-to-severe regurgitation, especially despite once-daily PPI treatment, should be considered for minimally invasive treatment with MSA rather than increased PPI therapy. (Clinical trial registration number: NCT02505945.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
53
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 39 publications
1
53
1
2
Order By: Relevance
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…). A total of 39 full‐text papers, published between 2008 and 2019, were finally included. The 39 articles consisted of one RCT, five comparative cohort studies (2 prospective and 3 retrospective), three comparative case–control studies, 25 case series (14 prospective, 11 retrospective) and five case reports ( Fig .…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies (1 RCT, 5 cohort and 3 case–control studies) included a comparator group ( Tables and ), although only one was randomized. Of these, seven compared MSA with antireflux surgery, one compared different types of dissection technique for MSA, and the RCT compared MSA with PPIs. Five, including the RCT, reported differences in patient baseline demographics, including hernia size, obesity, age, DeMeester score and disease severity, which were not accounted for in analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In the first study of 152 GERD patients randomized 2:1 to BID PPIs (N ¼ 102) or laparoscopic MSA (N ¼ 50), 89% of surgically treated patients (42/47) reported relief of regurgitation compared with 10% of BID PPI (omeprazole 20 mg) group (10/101) (P < .001) at 6 months. 11 As a physiological confirmation, a normal number of reflux episodes and acid reflux exposure measured by impedance pH testing was recorded in 91% and 89% of MSA patients, respectively, compared with 58% and 75% of BID PPI patients. The current study in Clinical Gastroenterology and Hepatology 12 extends the original study for 1 year, allowing patients not responding to PPIs to cross over to surgery.…”
mentioning
confidence: 88%
“…The procedure is associated with improvement in symptom scores and reduced need for PPI therapy but not with consistent reduction in esophageal acid exposure. 38 Roux-en-Y gastric bypass is a surgical option for morbidly obese patients. A prospective study with 53 patients showed an improvement in GERD symptoms, refl ux esophagitis, and esophageal acid exposure for more than 3 years following bypass.…”
Section: Young and Colleaguesmentioning
confidence: 99%